Separation of rennin-like enzyme from aflatoxins in Aspergillus flavus and A. parasiticus extracts - and AMAD ABDL-KHARIM, H.A. HADWAN, S.R. ALANI, Z.M. JAFFER (Indian Phytopathology, 2002)
Aflatoxins (B1, B2, G1, G2) and rennin-like enzyme, elaborated from 3 strains of A. flavus and 1 of A. parasiticus, grown in liquid media, were separated from each other. An ultra filtration method was preferable to that of protein precipitation by ammonium sulfate alone or along with dialysis, due to its efficiency, profitable application and common use in industry. There were few differences among the strains in terms of enzyme production but large differences were recorded regarding the production of aflatoxins. Aflatoxin concn were determined by HPLC before and after the partial purification of rennin-like enzyme.